Tryptogalinin is a tick Kunitz serine protease inhibitor with a unique intrinsic disorder - Valdés, James J; Schwarz, Alexandra; Cabeza de Vaca, Israel; Calvo, Eric; Pedra, Joao H F; Guallar, Victor; Kotsyfakis, Michalis (PloS one, 2013)
BACKGROUND: A salivary proteome-transcriptome project on the hard tick Ixodes scapularis revealed that Kunitz peptides are the most abundant salivary proteins. Ticks use Kunitz peptides (among other salivary proteins) to combat host defense mechanisms and to obtain a blood meal. Most of these Kunitz peptides, however, remain functionally uncharacterized, thus limiting our knowledge about their biochemical interactions. RESULTS: We discovered an unusual cysteine motif in a Kunitz peptide. This peptide inhibits several serine proteases with high affinity and was named tryptogalinin due to its high affinity for β-tryptase. Compared with other functionally described peptides from the Acari subclass, we showed that tryptogalinin is phylogenetically related to a Kunitz peptide from Rhipicephalus appendiculatus, also reported to have a high affinity for β-tryptase. Using homology-based modeling (and other protein prediction programs) we were able to model and explain the multifaceted function of tryptogalinin. The N-terminus of the modeled tryptogalinin is detached from the rest of the peptide and exhibits intrinsic disorder allowing an increased flexibility for its high affinity with its inhibiting partners (i.e., serine proteases). CONCLUSIONS: By incorporating experimental and computational methods our data not only describes the function of a Kunitz peptide from Ixodes scapularis, but also allows us to hypothesize about the molecular basis of this function at the atomic level.
Keywords: Tryptases; Animals; Arthropod Proteins; Serine Proteinase Inhibitors; cystein; klíště; sekvenční homologie aminokyselin; Protein Structure, Tertiary; Sequence Homology, Amino Acid; Rhipicephalus; Amino Acid Motifs; terciární struktura proteinů; lidé; Molecular Sequence Data; rekombinantní proteiny; Recombinant Proteins; inhibitory serinových proteinas; Salivary Proteins and Peptides; Models, Molecular; Phylogeny; molekulární sekvence - údaje; molekulární modely; Cysteine; zvířata; proteiny členovců; fylogeneze; aminokyselinové motivy; slinné proteiny a peptidy; tryptasy; Ixodes; Humans